PERBEDAAN PERTUMBUHAN BAKTERI STREPTOCOCCUS MUTANS DALAM PLAK SEBELUM DAN SESUDAH BERKUMUR AIR KELAPA HIJAU PADA PEROKOK DEWASA - Anses Warman; Eriyati Eriyati; Ika Ifitri; Arnetty Arnetty (HUMAN CARE JOURNAL, 2023)
Dental and oral health problems that most people suffer from are dental caries, one of which can affect dental caries is plaque which is an ideal place for the growth of bacteria that can produce acid. The nicotine content in cigarettes can increase the growth of Streptococcus mutans bacteria in cavities. mouth, Green Coconut Water has antimicrobial properties so it can be used as an alternative mouthwash for adult smokers. This study aims to determine the differences in the growth of Streptococcus Mutans bacteria in plaque before and after gargling with green coconut water in adult smokers. The research design used was a quasy experiment, that is, giving the experimental group the treatment of gargling using green coconut water. The way of taking the sample is by random sampling. Statistical analysis of the Paired t test. α = 0.05. Conclusions from this study There is a significant difference in the growth of Streptococcus mutans bacteria in plaque before and after gargling green coconut water in adult smokers.